Influence of anticardiolipin antibodies on immediate patient outcome after myocardial infarction. Issue 12 (December 1993) - Raghavan, C; Ditchfield, J; Taylor, R J; Haeney, M R; Barnes, P C
Abstract : AIMS–To determine whether the presence of anticardiolipin antibodies in patients with suspected myocardial infarction is predictive of complications during hospital stay or after discharge. METHODS–Anticardiolipin antibodies were serially measured in a cohort of 111 patients, from the time of admission to the coronary care until till eight weeks after discharge. Associations with fatal and non-fatal cardiac complications were documented. RESULTS–The incidence of raised titres of IgG and IgM anticardiolipin antibodies (ACA) in patients with myocardial infarction was comparable with that in patients with ischaemic heart disease. ACA titres in patients with a previous myocardial infarct were not significantly different from those found in patients without a previous history of infarction. Over the period of the study, ACA titres in the myocardial infarct group did not change significantly from those recorded on admission, nor did those patients with raised ACA titres have a higher prevalence of complications in hospital or in the early period after discharge. CONCLUSIONS–There is no evidence that patients with an acute or previous myocardial infarct have higher ACA titres than those found in patients with ischaemic heart disease. Raised ACA titres soon after myocardial infarction do not influence immediate patient outcome.